2008 IEEE 35th International Conference on Plasma Science 2008
DOI: 10.1109/plasma.2008.4590818
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electric fields (PEF) applications in food processing - process and equipment design and cost analysis

Abstract: The impact of pulsed electric fields (PEF) on plant and animal as well as microbial cell membranes was investigated. Electric field strength, energy input and treatment temperature were identified as key processing parameters. A critical field strength of 0.3 to 0.5 kV/cm for plant and animal and 10 to 15 kV!cm for microbial cells was observed.It was shown that extractability of fruit and vegetable juices and intracellular compounds can be enhanced after a PEF treatment. An increase of up to 7 % of apple juice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 1 publication
3
33
0
4
Order By: Relevance
“…Changes in tissue integrity were also indirectly supported by Töpfl [5] who noted that PEF had an impact on sample conductivity and weight loss.…”
Section: Case Study 5: Pef In Meat Tenderisationmentioning
confidence: 79%
See 1 more Smart Citation
“…Changes in tissue integrity were also indirectly supported by Töpfl [5] who noted that PEF had an impact on sample conductivity and weight loss.…”
Section: Case Study 5: Pef In Meat Tenderisationmentioning
confidence: 79%
“…Several microscopic studies have demonstrated physical changes in meat structure caused by PEF [1][2][3][4][5]. Changes in tissue integrity were also indirectly supported by Töpfl [5] who noted that PEF had an impact on sample conductivity and weight loss.…”
Section: Case Study 5: Pef In Meat Tenderisationmentioning
confidence: 90%
“…Varity of foods have been treated by PEF for increasing the production, prolonging the quality guarantee period and saving energy [12][13][14][15][16][17]. Part of the recent research is summarized in table 1.…”
Section: Design Considerations Of the Generatormentioning
confidence: 99%
“…An increased juice yield plays an important role in juice industry. In general mechanical, enzymatic or temperature based methods were used to rupture the apple cells for a facilitated extracting, but mostly they lead to a degradation of important juice components as well as a high energy consumption (Toepfl 2006). A PEF treatment of the apples increases the yield from 1,7 to 7,7 % in comparison to an enzymatic treatment (4,2 %) (Schilling et al, 2007) and reduces the energy consumption.…”
Section: Influence Of Pef On Mass Transfermentioning
confidence: 99%
“…For the treatment of sliced apples, the energy consumption is 12,5 ±0,5 kJ/kg and for whole apples 7,9±0,4 kJ/kg (Grimi et al, 2011). The typical energy requirement is in a range of 60-100 kJ/kg; heating, freezing/thawing: >100 kJ/kg) the energy consumption is very low (Toepfl 2006). For tissue softening, where a lower extent of cell disintegration is required, the typical specific energy input for a PEF treatment is in a range of 1 kJ/kg.…”
Section: Process and Equipment Designmentioning
confidence: 99%